Pengembangan Modul Pembelajaran Biologi Berbasis Inkuiri Terbimbing pada Materi Ekosistem untuk Siswa Kelas X SMAN 2 Menggala: (Development Of Guided Inquiry-Based Biology Learning Modules On Ecosystem Materials For Class X Students Of SMAN 2 Menggala) - Vienna Restiana; Suhendi Suhendi; Yudiyanto Yudiyanto; Nasrul Hakim (BIODIK, 2022)
The purpose of this study was to determine the characteristics of the guided inquiry-based biology learning module on ecosystem material for class X high school students, to determine the feasibility of the guided inquiry-based biology learning module on ecosystem material for class X high school students, and to find out the responses from biology teachers and students. In terms of the results of the questionnaire assessment. This study uses the Research and Development method developed by Sugiyono to develop printed learning media in the form of modules. Before testing the product, the finished initial product is then validated by experts. The final result of the material expert got a percentage of 86% with the "Very Eligible" criteria, and media expert validation got a percentage of 92% with the "Very Eligible" criteria. After that, a limited-scale trial was conducted, the results of the biology teacher's response were 95.41% and from 10 students the percentage was 90.50%. In conclusion, the module developed has the criteria of "Very Good" and is suitable for use in the learning. Key words: Learning Module, Guided Inquiry, Ecosystem Â  Abstrak. Tujuan penelitian ini adalah untuk mengetahui karakteristik modul pembelajaran biologi berbasis inkuiri terbimbing pada materi ekosistem untuk siswa kelas X SMA, untuk mengetahui kelayakan modul pembelajaran biologi berbasis inkuiri terbimbing pada materi ekosistem untuk siswa kelas X SMA, dan untuk mengetahui tanggapan dari guru biologi dan peserta didik ditinjau dari hasil penilaian angket. Penelitian ini menggunakan metode Research and Development yang dikembangkan oleh Sugiyono untuk mengembangkan media pembelajaran cetak dalam bentuk modul. Sebelum menguji produk, produk awal yang telah selesai kemudian divalidasi oleh para ahli. Hasil akhir dari ahli materi mendapatkan presentase 86% dengan kriteria â€œSangat Layakâ€, dan validasi ahli media mendapatkan presentase 92% dengan kriteria â€œSangat Layakâ€. Setelah itu dilakukan uji coba skala terbatas, hasil respon guru biologi 95,41% dan dari 10 siswa persentasenya 90,50%. Kesimpulannya, modul yang dikembangkan memiliki kriteria â€œSangat Baikâ€ Â dan layak untuk digunakan dalam proses pembelajaran. Kata kunci: Modul Pembelajaran, Inkuiri Terbimbing, Ekosistem